Recoverable concealed data aggregation for privacy preserving in wireless sensor networks - Wu, Dapeng; Tang, Jichao; Sun, Qingwen; Wang, Ruyan (2012 5th International Conference on Biomedical Engineering and Informatics, 2012)
Data aggregation is one of the key technologies in the wireless sensor networks (WSNs). Moreover, the privacy of data must be preserved in WSNs. A privacy preserving data aggregation scheme is designed in the energy efficient manner in this paper. Based on the reflexivity property of the XOR operation, the original data obtained from sensor is sliced into several segments. Further, these slices are aggregated and transmitted to the sink node with the aid of nodes in the same region. Finally, the data can be reconstructed by the sink node according to the relation between slices. With our simple integrity check method, the accuracy of reconstructed data can be enhanced. We evaluate the performance of our proposed scheme in terms of communication overhead, computation overhead and privacy preservation, and these performances are compared with the typical data aggregation scheme, CPDA and iPDA respectively. Results show that the overhead can be reduced effectively by our proposed mechanism, and the scalability can also be guaranteed.